Karyotypes and DNA content in Bignoniaceae - Piazzano, Marianela (2015)
Cytogenetic studies in 22 Bignoniaceae species were performed. Most taxa are from Argentina, one from Brazil, and two are cultivated (from South Africa and USA). All data are new, including first counts for Bignonia binata, Handroanthus ochraceus, Tabebuia aurea and the genus Podranea. Most taxa are diploid (2n= 40): members of tribes Bignonieae (Adenocalymma, Amphilophium, Bignonia, Cuspidaria, Dolichandra, Fridericia, and Tynanthus), Catalpeae (Catalpa) and the Tabebuia alliance (Handroanthus and Tabebuia). Dolichandra unguis-cati and Handroanthus chrysotrichus were polyploid (2n= 80). Tribes Jacarandeae (Jacaranda) and Tecomeae (Tecoma) were unusual (with 2n= 36), whereas Podranea ricasoliana(Tecomeae) had 2n=38. The basic numberx= 20 is proposed as the base number for the family. Chromosomes are small. The average length was 1.21 μm. Average haploid karyotype length was 28.13μm, ranging from 18.63 in Dolichandra cynanchoidesto 37.63 in D. unguis-cati. Type m chromosomes were the most common. One to five sm pairs were found in 16 species and one st pair inCuspidaria convolutaandPodranea ricasoliana. One to four microsatellites, in long or short arms, were detected in nine species. Karyotypes are symmetrical. Asymmetry indices ranges were: A1= 0.11?0.23, A2= 0.14?0.22. The karyotypes of P. ricasoliana and C. convoluta were the most asymmetrical. Most species were karyologically indistinguishable based on conventional staining, but some could be distinguished by a combination of traits. 1C nuclear DNA content for 12 species were within the range 0.64?2.02 pg. In Bignoniaceae there is a common karyotypical pattern of mostly small m chromosomes with few cryptic chromosomal rearrangements.